SINTESIS DAN IDENTIFIKASI STRUKTUR SENYAWA 3-(3,5-DINITROBENZOIL)-1-FENILTIOUREA SEBAGAI KANDIDAT ANTIKANKER - Susanti Susanti; Ruswanto Ruswanto; Muharam Priatna (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Perjuangan Tasikmalaya, 2018)
Thiourea derivatives are known to be potential anticancer agents. 3-(3,5-dinitrobenzoyl)-1-phenylthiourea as a thiourea derivatives has been synthesized through acylation between 3,5-dinitrobenzoyl chloride and 1-phenylthiourea in tetrahydrofuran with triethylamine ascatalyst through reflux process with stirring for 6 hours. The percentage of yield was13,86%. The purity of the product was shown by the single spot on the TLC and narrowrange of melting point. The structure identification results with UV spectrophotometry, IRspectroscopy and 1HNMR spectroscopy showed that the structure of the product wasappropriate to the prediction.